2015
DOI: 10.3109/08880018.2015.1034819
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucositis in Pediatric Acute Lymphoblastic Leukemia Patients: Evaluation of Microbiological and Hematological Factors

Abstract: the presence of HSV, platelet count, and Candida spp. presence at D14 of ALL induction treatment is associated with increased severity of mucositis in children and adolescents. At D56 of ALL treatment, mucositis severity was associated with neutrophil count, HSV presence, and previous presence of HSV (at D14).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 31 publications
3
37
3
11
Order By: Relevance
“…The WBC and neutrophil counts were monitored over time as previous studies have demonstrated that blood counts, especially absolute neutrophil count, are associated with OM onset and severity . In our study, the efficacy of PBM was not influenced or mediated by alterations in neutrophil counts, as these did not differ in the two groups.…”
Section: Discussionsupporting
confidence: 49%
“…The WBC and neutrophil counts were monitored over time as previous studies have demonstrated that blood counts, especially absolute neutrophil count, are associated with OM onset and severity . In our study, the efficacy of PBM was not influenced or mediated by alterations in neutrophil counts, as these did not differ in the two groups.…”
Section: Discussionsupporting
confidence: 49%
“…More recent studies [11,12,26] have revealed a relationship between HSV and CIOM; however, the present study identified HSV-1 as a risk factor for CIOM that was independent of age, sex, treatment stage, and type of disease. The reason for the difference in the results of earlier studies (i.e., no relationship of HSV to CIOM) [15][16][17] versus more recent studies (i.e., a strong association of HSV with CIOM) [11,12,26] could be attributed to the more frequent use of antimicrobial agents in more recent days [27]. Because antibiotics or antifungal agents are so commonly used either prophylactically or therapeutically, it is more difficult for bacteria or fungi to cause CIOM.…”
Section: Discussioncontrasting
confidence: 95%
“…The WBC and neutrophil counts were monitored over time as previous studies have demonstrated that blood counts, especially absolute neutrophil count, are associated with OM onset and severity. 23 In our study, the efficacy of PBM was not influenced or mediated by alterations in neutrophil counts, as these did not differ in the two groups.…”
Section: Discussionsupporting
confidence: 45%